دور الاعلام الاجتماعي لتنمية مهارة الكلام لغير الناطقين بالعربية لدى طلبة جامعة حلبجة - Hama Karim, Najmadin Abdul Karim; Chik, Abdul Rahman; Abdullah, Mohd Ikhwan (Tikrit University College of Islamic Sciences, Iraq, 2023)
هدف من هذا البحث إلى التعرف على دور الاعلام الاجتماعي لتنمية مهارة الكلام لغير الناطقين بالعربية لدى طلبة جامعة حلبجة، ولتحقيق أهداف البحث اتبع الباحث المنهج الوصفي التحليلي. إن اللغة وسيلة التواصل والكلام بين الشعوب والاعلام له دور كبير في اتساع هذا التواصل، يعد الكلام من إحدى المهارات التي واجه الطلبة صعوبات التكلم باللغة العربية في جامعة حلبجة لأن الطلبة قضوا معظم وقتهم في عرض العناصر النحوية والصرفية وإلى غير ذلك، ولم تكن لديهم الوقت الكافي لممارسة مهارة الكلام في الفصل، ولم تكن مهارة الكلام لديهم تصل إلى مستوى عالي، لأن هذه الدراسة لا تلبي طموح الناطقين بغيرها بل تشمل الذين يجيدون اللغة العربية، إلا أن هناك بعض الصعوبات تواجه طلبة جامعة حلبجة وهي لغتهم الأم الكوردية وليست اللغة العربية. خلص البحث على دور الاعلام الاجتماعي خصوصا مواقع التواصل الاجتماعي لديه دوركبير لتطوير وتوسع اللغة العربية لدى الطلبة جامعة حلبجة الذين لم ينطق بها، لأن عصر التقدم والعولمة التي اتجه وانتشر في بلادنا كوردستان العراق وإنغماس الجيل الجديد في استخدام الوسائل والتكنلوجيا والتطور كالاجهزة المحمولة والجوال الذكية، جعل الطرق التقليدية غير مجدية في مجال التعليم والتعلم، لذا دور الاعلام في هذا المجال يظهر الإثارة والتشويق والفضول لعناصر البيئة التعليمية المتعددة منها المواقع التواصل الاجتماعي والاعلام الاجتماعي بشكل كامل الفعالة بين المعلم والمتعلم، صارت تلبية للاحتياجات الفرد والمجتمع، لذا حاول الباحث من خلال البحث ان يبين المشاكل والاحتياجات المطلوبة من خلال دور الاعلام الاجتماعي لكي يكون الطالب مؤهلا ومتمكنا من حيث اللغة والكلام باللغة العربية، لكي يستفيد من الامكانيات المتوفرة فيها ليصبح الطالب بعد تخرجه عنصرا كفوءا مؤهلا يستافد من نفسه والآخرين في البناء وتنظيم المجتمع في مجالاته المختلفة، ولضمان وحفظ مصالحه وممارسة حقوقه. الكلمات المفتاحية: اللغة العربية - الاعلام الاجتماعي – مهارة الكلام – الناطقين بغيرها. Abstract The aim of this research is to identify the role of social media in developing the speaking skill of non-Arabic speakers at the University of Halabja, and to achieve the objectives of the research, the researcher followed the analytical descriptive approach. Language is a means of communication and speech between peoples and the media has a great role in expanding this communication. Speech is one of the skills that students faced difficulties in speaking Arabic at the University of Halabja because students spent most of their time presenting the grammatical and morphological elements and so on, and they did not have enough time To practice the skill of speaking in the classroom, and their speaking skill did not reach a high level, because this study does not meet the aspirations of non-native speakers, but rather includes those who are fluent in the Arabic language, but there are some difficulties facing the students of Halabja University, whose mother tongue is Kurdish, not the Arabic language. The research concluded on the role of social media, especially social networking sites. It has a great role to develop, expand and develop the skill of speaking the Arabic language among students at the University of Halabja, because the era of progress and globalization that has spread in our country, Kurdistan, Iraq, and the immersion of the new generation in the use of means, technology and development such as mobile devices and smart mobile, make traditional methods It is useless in the field of education and learning, so the role of the media in this field shows the excitement, suspense and curiosity of the various elements of the educational environment, including social networking sites and social media fully effective between the teacher and the learner, it has become a response to the needs of the individual and society, so the researcher tried through research to show the problems and needs Required through the role of social media in order for the student to be qualified and proficient in terms of language and speech in the Arabic language, in order to benefit from the capabilities available in it so that the student becomes, after his graduation, a qualified and qualified element that benefits himself and others in building and organizing society in its various fields, and to ensure and preserve his interests and exercise his rights.